Accounting for the Bitcoin: accountability, neoliberalism and a correspondence analysis. Issue 1 (11th April 2016) - Ram, Asheer; Maroun, Warren; Garnett, Robert
Abstract : Purpose: Given its innovative characteristics and increasing popularity, the Bitcoin, and other virtual currencies, are expected to become mainstream, leading to the need for a generally accepted accounting treatment. Currently, however, there are no accounting standards which offer guidance on the recognition and measurement of these virtual currencies. To this end, the purpose of this paper is to determine a conceptual approach for accounting for the Bitcoin, grounded in the theories of neoliberalism and stewardship. Design/methodology/approach: The research adopts an interpretive mixed-method approach. The relevant literature is analysed to identify key characteristics of the Bitcoin. These, as well as the elements of accounting policies inspired by neoliberalism and stewardship, form row and column headings in a correspondence matrix completed by 40 financial reporting experts. The correlations between rows and columns (developed using principal component analysis) are used to identify possible recognition and measurement requirements for the Bitcoin. Semi-structured interviews are used to complement the correspondence analysis. Findings: The correspondence analysis and interviews reveal an emphasis on cost and fair value proposed by models grounded in stewardship and neoliberalism, respectively. The primary factor at work is the need to account for the underlying economics of the unit of account, something which is informed heavily by an organisation's business model. Cost and fair value may be conceptual opposites, but in the eyes of respondents, these need to be used to achieve the single goal of communicating the economic rationale for holding the Bitcoin. Research limitations/implications: The study is based on a purposefully selected sample of experts and lacks the exploratory potential of purely qualitative research. Nevertheless, it makes novel use of a correspondence analysis to provide an initial frame of reference for developing an accounting policy for unusual transactions and balances. Originality/value: The paper is the first to provide a normative perspective on the accounting for this poorly understood "currency". It also adds to the limited body of interpretive accounting research which dispenses with traditional finance paradigms and positivist models to provide practical recommendations. Finally, the paper offers an innovative approach, using a correspondence analysis and detailed interviews, for developing an accounting policy for transactions not specifically within the scope of existing accounting standards.